India after the 2014 general elections: BJP dominance and the crisis of the third party system. Issue 3 (27th May 2019) - Schakel, Arjan H.; Sharma, Chanchal Kumar; Swenden, Wilfried
ABSTRACT: This article critically assesses claims that India has entered a new party system after the 2014 general elections, marked by renationalisation with the BJP as the new 'dominant' party.' To assess these claims, we examine the electoral rise of the BJP in the build-up to and since the 2014 general elections until the state assembly elections in December 2018. Overall, we argue that despite the emerging dominance of the BJP, a core feature of the third party system -a system of binodal interactions- has remained largely intact albeit in a somewhat weaker form. Furthermore, by comparing the post 2014 Indian party system with key electoral features of the first three party systems, we conclude that the rise of the BJP has thrown the third-party system into crisis, but does not yet define the consolidation of a new party system.